Relationship between α‐genus human papillomavirus and non‐genital seborrheic keratosis: Report of new cases and updated review. (23rd January 2022) - Nellessen, Tobias; Aoki, Rui; Kammerbauer, Claudia; Clanner‐Engelshofen, Benjamin M.; French, Lars E.; Reinholz, Markus
Abstract: Background: Seborrheic keratoses (SK) are the most common acquired benign tumor that affects middle‐aged or older adults with great cosmetic concern. Clinical and histopathological similarities of SK and common warts have been addressed by investigating the possible presence of human papillomavirus (HPV) DNA in SK. Previous studies suggested the association between α‐genus HPV and SK located on genital skin, whereas the causal relationship between α‐HPV and non‐genital SK remains controversial. Aim: This study aimed to clarify the pathogenic involvement of α‐HPV in the development of non‐genital SK. Methods: We analyzed α‐HPV DNA prevalence and HPV genotypes using a PCR‐based microarray on 51 skin samples presenting with histologically confirmed SK without any malignant changes. Correlation between the histological subtype of SK and their HPV DNA‐positive reactivity was also evaluated. Results: Of 51 non‐genital SK, two (3.9%) skin samples were positive for α‐HPV DNA; high‐risk HPV 31 and low‐risk HPV 42 were found. Evaluation of HPV prevalence in different histological types of SK showed that both HPV‐positive cases were acanthotic type; 14.3% of acanthotic SK lesions were positive, while all of the other types were negative for α‐HPV. Conclusions: This study demonstrates that α‐HPV positivity is very rare in common non‐genital SK. The rare α‐HPV‐positive SK lesions histologically belonged to the acanthotic type, implying a potential impact of HPV infection on epidermal hyperproliferation. Although a possible association cannot be excluded, our findings suggest that α‐HPV is not a major causative factor for non‐genital SK.